Genetically Modified T Cells to Target Glioblastoma - Krebs, Simone; Rodríguez-Cruz, Tania G.; DeRenzo, Christopher; Gottschalk, Stephen (Frontiers in Oncology, 2013)
Despite advances in surgical procedures, radiation- and chemotherapy the outcome for patients with glioblastoma (GBM) remains poor. While GBM cells express antigens that are potentially recognized by T cells, GBMs prevent the induction of GBM-specific immune responses by creating an immunosuppressive microenvironment. The advent of gene transfer has allowed the rapid generation of antigen-specific T cells as well as T cells with enhanced effector function. Here we review recent advances in the field of cell therapy with genetically modified T cells and how these advances might improve outcomes for patients with GBM in the future.